PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS WORDWALL UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG MATEMATIKA PADA SISWA KELAS 1 SEKOLAH DASAR - Aidhella Tyas Permatasari; Arita Marini; Waluyo Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning media based on Wordwall to improve mathematical counting skills among first-grade elementary school students. The research problem focuses on students’ low arithmetic abilities and the lack of engaging learning media suitable for early childhood characteristics. The research method used is Research and Development (R&D) with a quantitative approach using a one-group pretest-posttest design. The research instruments consisted of a 10-item multiple-choice test for pretest and posttest, and a student response questionnaire regarding the use of Wordwall. The sample in this study involved 20 first-grade students from SDN Tengah 07 Jakarta Timur. The media was developed using the Wordwall platform with the "Open the Box" template, presenting basic addition problems in an interactive quiz format. The results showed that the average score increased from 74.65 (pretest) to 90.45 (posttest). The paired sample t-test showed a significance value of p < 0.001, indicating a statistically significant difference before and after the intervention. The N-Gain score was 74.59%, which falls into the effective category. Additionally, students’ responses to the use of Wordwall indicated high enthusiasm and positive perceptions in terms of visual appeal, ease of use, and motivation to learn. Based on these findings, it can be concluded that Wordwall media is effective in improving counting abilities in mathematics for first-grade elementary school students.